Registration of 'Roberts' Soybean with High Yield and Good Quality. Issue 1 (11th October 2013) - Jiang, Guo-Liang; Scott, Roy A.; Green, Marci; Wang, Xianzhi; Bhusal, Siddhi; Zhang, Jiaoping; Hall, Nicholas; Agoub, Mukhtar; Tirumalaraju, Sivananda
Abstract : Soybean [ Glycine max (L.) Merr.] cultivar Roberts (Reg. No. CV‐510, PI 667737) was developed at South Dakota State University (SDSU), Brookings, SD, and released by the South Dakota Agricultural Experiment Station in April 2013. It was released because of its high yield potential, good seed quality, and resistance to Phytophthora root rot ( Phytophthora sojae Kaufmann & Gerdemann), as well as adaptability to South Dakota and similar latitudes. Roberts, originally designated as SD03‐2154, is a maturity group (MG) 0 cultivar (relative maturity 0.7–0.8). It originated from the F5 progeny of a single F4 plant derived from the cross of 'Surge' × A96‐492041 with early generations advanced by a modified single‐seed descent method. It was initially evaluated for yield and quality in the SDSU soybean breeding program, and advanced testing was further conducted in the USDA Northern Regional Uniform Tests (UTs) and the South Dakota Crop Performance Tests (CPTs) during 2006 to 2012. Over 35 environments, the yield of Roberts averaged 3404.6 kg ha −1, which was 4.3% higher than the check cultivar Surge (3264.2 kg ha −1 ). In the UTs (23 year‐locations), Roberts averaged a 4.3% higher yield than the check cultivar Sheyenne. Average protein and oil concentrations of Roberts were 351.1 and 178.6 g kg −1 at 13% moisture, compared with Surge (362.0 and 175.9 g kg −1 ) and Sheyenne (339.1 and 178.7 g kg −1 ). In addition, it exhibited resistance to races 4 and 7 of P. sojae . Roberts is a conventional, high‐yield, good‐quality, MG 0 cultivar with the allele Rps1k for resistance to P. sojae, and thus it is a good replacement for Surge for producers of non–genetically modified soybeans in South Dakota and similar latitudes.